Proverbs in Action: Exploring Their Meaning and Internalization in Manggarai's Teing Hang Rituals - Agustinus Manfred Habur (Yayasan Keluarga Guru Mandiri, 2025)
Manggarai's Teing Hang rites provide as a live medium for the internalization and expression of ancestral proverbs that govern social values and collective behaviours. The purpose of this study is to uncover the significance of the proverbs used in the Teing Hang ritual and to comprehend how the Manggarai community internalizes these expressions. Data were gathered utilizing a qualitative method incorporating elders, cultural experts, and the younger generation through in-depth interviews and interactive observations. Thematic data analysis was used to identify and comprehend the meaning by utilizing semiotic and pragmatic theories. The data triangulation procedure was also utilized to strengthen the validity and reliability of the research findings. The findings demonstrate that Teing Hang proverbs serve as a tool for ritual communication as well as having deep symbolic connotations that enhance the community's social, spiritual, and cultural relations. Learning to live with these local expressions offers a window into the difficulties the younger generation has upholding traditional norms in the face of globalization. By incorporating local culture into teaching and learning instruction, these findings are expected to contribute to the development of understanding about the importance of preserving culture and language in the modern era.